Project Risk Based Evaluation for Infrastructure Works in Qatar: Highway Projects - Abd Rahman, Nor Rozaini (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The implementation of a project for infrastructure works such as highways, bridges, flyovers, underpasses, tunnels, etc. can be complexed and unique. This has always required a proper project management system that includes the conception and initiation, planning, execution, performance/monitoring and close-out phases. The construction risks identification and mitigation processes are critical and essential at the beginning of the project phase i.e. planning phase, in order to deal with the risks and avert them as to minimize effects to the work progress. The construction risks include additional works that could contribute to the project cost overrun and delay the works progress, any political uncertainty including a blockade imposed by a group of countries towards a particular country, and a possibility of introduction of new taxation by the government i.e. Value Added Tax (VAT) which could definitely affect the material, labor, service and machinery prices. This research paper identifies the construction risks which have affected the implementation of certain ongoing and completed infrastructure works undertaken by the Public Works Authority (PWA or ASHGHAL) in Qatar in recent years. The research included and focused on the importance of project evaluation formalization through identification of obstacles and challenges associated with project risks. There could be a possibility that the identified projects were not fully assessing the significant risk factors during the feasibility studies. Based on a literature review, questionnaires, structured interviews, unstructured interviews, and detailed case studies, it has been established that the most critical construction risks were the design changes, additional works, land acquisition, new requirements, contractors’ non-performance, and interfacing works. Most of the experts indicated that the design changes could be reduced by defining and establishing detailed scope of works and specifications during the design stage. An early project coordination with the key stakeholders should be implemented to ensure that the detail information, requirements and any future interfacing works are assessed and updated for potential clashes and resolutions.